Edukasi Peranan Sertifikasi Halal Bagi Pelaku Usaha Kuliner Makanan Pada Sektor Pariwisata Di SMP Negeri 3 Medan - Furqan; Mega Hernawati Harefa; Rijal Allamah Harahap (Jurnal Masyarakat Indonesia (Jumas), 2025)
Education on the role of halal certification of products is very important in order to open horizons for food culinary businesses and the tourism sector so that with halal certification they are ready to compete and gain a larger market share. The implementation of this community service activity was carried out on food culinary business actors assisted by the Persati Beken Community at SMP Negeri 3 Medan. The method used by the service team is the method of education and socialization of the halal product assurance system. The results of this community service are that all participants / food culinary business actors respond positively to halal certification education activities and participants want this activity to be carried out in continuity so that they are assisted in obtaining halal certification for the products of food culinary business actors assisted by the Persati Beken Medan Community